2022
DOI: 10.1186/s12920-022-01284-y
|View full text |Cite
|
Sign up to set email alerts
|

Dysferlinopathy misdiagnosed with juvenile polymyositis in the pre-symptomatic stage of hyperCKemia: a case report and literature review

Abstract: Background Dysferlinopathy encompasses a group of rare muscular dystrophies caused by recessive mutations in the DYSF gene. The phenotype ranges from asymptomatic elevated serum creatine kinase (hyperCKemia) to selective and progressive involvement of the proximal and/or distal muscles of the limbs. Bohan and Peter criteria are the most widely used for the diagnosis of polymyositis, but they have limitations and can misclassify muscular dystrophies with inflammation as polymyositis. Most dysfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Recent papers reported that patients with asymptomatic hy-perCKemia may have muscular dystrophy [Alcahut-Rodríguez et al, 2020;Lee et al, 2021]. It has been emphasized that patients with pathogenic changes in LGMD-related genes may present with asymptomatic CK elevation [Lee et al, 2021;Alcahut-Rodríguez et al, 2020;Contreras-Cubas et al, 2022]. There is a growing body of literature that recognizes that genetic analysis methods can detect patients while they are asymptomatic [Alcahut-Rodríguez et al, 2020;Lee et al, 2021].…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers reported that patients with asymptomatic hy-perCKemia may have muscular dystrophy [Alcahut-Rodríguez et al, 2020;Lee et al, 2021]. It has been emphasized that patients with pathogenic changes in LGMD-related genes may present with asymptomatic CK elevation [Lee et al, 2021;Alcahut-Rodríguez et al, 2020;Contreras-Cubas et al, 2022]. There is a growing body of literature that recognizes that genetic analysis methods can detect patients while they are asymptomatic [Alcahut-Rodríguez et al, 2020;Lee et al, 2021].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathological findings on routine histopathological and immunohistochemical stains and heterogeneity of clinical manifestations make it difficult to diagnose dysferlinopathy [19]. Several patients with dysferlinopathy have been previously misdiagnosed with inflammatory myopathy [19,20] and juvenile polymyositis [21,22]. In the case of dysferlinopathy, most patients received muscle biopsies for increased inflammatory responses [23,24], even those who were less affected clinically, suggesting that this sign is a relatively early feature [25].…”
Section: Discussionmentioning
confidence: 99%
“…[1]. Дисферлинопатия включает в себя пресимптоматический этап бессимптомного повышения уровня креатинкиназы (КК) в крови и манифестный этап, характеризующийся прогрессирующим поражением проксимальных и/ или дистальных мышц конечностей [2]. Различают пять основных фенотипов дисферлинопатии: дистальная миопатия Миоши (OMIM # 254130), поясно-конечностная мышечная дистрофия R2 (LGMD R2, OMIM # 253601); дистальная миопатия переднего ложа голени (дистальная, с началом в передней большеберцовой мышце (DMAT, OMIM # 606768); проксимально-дистальная форма (переходная форма) и врожденный фенотип [3].…”
Section: дисферлинопатияunclassified